ANALISIS KETAHANAN PANGAN RUMAH TANGGA PESERTA PROGRAM DESA MANDIRI PANGAN DI DESA SEI SIMPANG DUA KECAMATAN KAMPAR KIRI HILIR KABUPATEN KAMPAR - Fitrah, Wildan; Yulida, Roza; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Food security program is one of the important issues related to improve people welfare in villages. The objective of this study is analyse food security of participant households on food self-sufficency village programm in Sei Simpang Dua Village. The study uses both primary and secondary data using a survey method. Data were collected from 38 households participated in the program that taken by doing census and 30 traders related to the program using purposive sampling. The data were analyse to access the availability of food, household income, and household expenditure in the village. The results show that majority of food are available in the local market but were originated from outside the village. The households income on average are Rp 1.732.237,- while households expenditures are Rp 1.005.807.-. The low income level has provoked the average amount of calorie consumption only 1.266,10 kcal/capita/day. Keywords : food security, food availability, food access, income